Progesterone inhibits embryotoxic effect of the complement system - Nováková, Pavla; Zeman, Michal (Neuro endocrinology letters, 1999)
The complement system of normal human serum (NHS) manifests a strong, dose dependent embryotoxic potential when administered to chick embryos inducing, among others, also malformations of the brain. We have demonstrated, however, that the degree of complement-induced embryotoxicity varied remarkably in the course of the menstrual cycle of fertile healthy women, although the complement serum activity (CH100) exhibited no significant fluctuation. On the other hand, the variation of embryotoxicity appeared negatively associated with progesterone levels. Following our results high progesterone levels occurring physiologically in luteal phase of the menstrual cycle suppress the embryotoxic action of the complement system.